Separator and lithium secondary battery comprising the same

A separator with a nitrogen-containing polymer and barium sulfate coating addresses lithium secondary battery issues of high-temperature storage and gas generation, enhancing stability and life through reduced gas production and improved adhesion.

JP2025015505APending Publication Date: 2025-01-30SK INNOVATION CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024114994
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Lithium secondary batteries face issues with high temperature storage characteristics and increased gas generation, leading to potential fires and explosions due to volume expansion, which degrade performance and reduce battery life.

Method used

A separator comprising a porous base material with a coating layer containing nitrogen-containing water-soluble polymers and barium sulfate particles, which reduces gas generation and enhances high-temperature storage stability.

Benefits of technology

The separator provides excellent adhesion, low thermal contraction, and high capacity maintenance rates, improving high-temperature storage stability and extending battery life with reduced gas production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015505000001
    Figure 2025015505000001
  • Figure 2025015505000002
    Figure 2025015505000002
  • Figure 2025015505000003
    Figure 2025015505000003
Patent Text Reader

Abstract

To provide: a separator which is excellent in high-temperature storage stability and a capacity retention rate of a lithium secondary battery, and has a low resistance increase rate and significantly decreased gas emission; and a lithium secondary battery including the same.SOLUTION: Provided as one aspect is a separator including: a porous substrate; and a coating layer formed on one or both surfaces of the porous substrate. The coating layer includes a water-soluble crosslinked polyacrylamide-based binder and barium sulfate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a separator and a lithium secondary battery including the same. [Background technology]

[0002] In recent years, lithium secondary batteries have been required to have larger capacities so that they can be used in electric vehicles and energy storage devices. However, the larger the capacity of the lithium secondary battery, the higher the risk of fire and explosion. Therefore, various research projects are being conducted to improve this risk.

[0003] In a typical lithium secondary battery, a cell consisting of a negative electrode, a positive electrode, and a separator between the negative and positive electrodes is wound or stacked into a cylindrical shape, inserted into a pouch, and a liquid electrolyte is injected into the pouch to manufacture the battery. The electrolyte facilitates the transfer of charge between the electrodes and generally contains a non-aqueous organic solvent and a salt.

[0004] When a lithium secondary battery containing a commonly used non-aqueous organic solvent and salt is stored at high temperature for a long period of time, the lithium secondary battery may catch fire or explode due to various factors.

[0005] For example, in a lithium secondary battery using a carbonate-based organic solvent, a solid electrolyte interphase film (SEI film), which is a decomposition product of a solid electrolyte, is formed on the surface of the negative electrode, which may cause the decomposition of the carbonate-based organic solvent and generate gas inside the secondary battery. Alternatively, the electrolyte may react very sensitively to moisture and generate gas. Such gases include hydrogen gas (H2), carbon monoxide gas (CO), carbon dioxide gas (CO2), methane gas (CH4), hydrogen fluoride, hydrogen sulfide, etc., depending on the type of non-aqueous organic solvent and negative electrode active material.

[0006] The generation of gas causes the thickness to expand during charging, and if the lithium secondary battery is left at high temperatures in a fully charged state (charged to its maximum capacity), a side reaction may occur in which the electrolyte reacts with the surface of the negative electrode. This causes continuous gas generation, an increase in the internal pressure of the lithium secondary battery, and a decrease in performance, such as a shortened lifespan of the lithium secondary battery at high temperatures, due to the volume expansion.

[0007] Therefore, in order to improve the shortened life and the deterioration of performance, research is being conducted to change the constituent components of the electrolyte, change the type of the negative electrode material, and so on. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Registration No. 10-2436898 (2022.08.23) Publication Summary of the Invention [Problem to be solved by the invention]

[0009] According to one aspect of the present disclosure, an object is to provide a separator capable of improving both the high-temperature storage characteristics and the battery life of a lithium secondary battery.

[0010] Another object of the present invention is to provide a separator capable of significantly reducing the amount of gas generated, and a lithium secondary battery using the same.

[0011] The separator of the present disclosure and the lithium secondary battery including the same are widely applicable in the field of green technology such as electric vehicles, battery charging stations, solar power generation using other batteries, wind power generation, etc. In addition, the separator of the present disclosure and the lithium secondary battery including the same can be used in eco-friendly electric vehicles, hybrid vehicles, etc., for reducing air pollution and greenhouse gas emissions and preventing climate change. [Means for solving the problem]

[0012] One aspect of the present disclosure provides a separator comprising a porous substrate and a coating layer on one or both sides of the porous substrate, the coating layer comprising a nitrogen-containing water-soluble polymer and barium sulfate particles.

[0013] In one embodiment, the nitrogen-containing water-soluble polymer may include any one or more selected from the group consisting of polyvinylpyrrolidone, polyvinylpyrrolidone-based copolymers, and polyacrylamide-based resins.

[0014] In one embodiment, the polyacrylamide resin may be a copolymer including a unit derived from a (meth)acrylamide monomer and a unit derived from a comonomer.

[0015] In one embodiment, the polyacrylamide resin may include, but is not limited to, (a) a structural unit derived from a (meth)acrylamide monomer, (b) a structural unit derived from a (meth)acryl monomer containing a hydroxy group, and (c) a structural unit derived from a polyfunctional (meth)acrylamide monomer.

[0016] In one embodiment, the polyacrylamide resin may contain (a) structural units derived from 65 to 96 mol % of (meth)acrylamide monomers, (b) structural units derived from 3 to 34 mol % of (meth)acryl monomers containing a hydroxy group, and (c) structural units derived from 0.001 to 1 mol % of polyfunctional (meth)acrylamide monomers, but is not limited thereto.

[0017] In one embodiment, the polyacrylamide resin may have a weight average molecular weight of 100,000 to 2,000,000 g / mol, but is not limited thereto.

[0018] In one embodiment, the coating layer may further include, in addition to the barium sulfate particles, one or more inorganic particles selected from boehmite, alumina, silica, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO3, SnO2, CeO2, NiO, ZnO, ZrO2, Y2O3, and SiC, but is not limited thereto.

[0019] In one embodiment, the barium sulfate particles may have an average particle size of 200 to 1000 nm, but is not limited thereto.

[0020] In one embodiment, the barium sulfate particles may be a mixture of two or more types of particles having different average particle sizes, but is not limited thereto.

[0021] In one embodiment, the barium sulfate particles are a mixture of first barium sulfate particles having an average particle size of 200 to 500 nm and second barium sulfate particles having an average particle size of 500 to 1000 nm, and the difference in average particle size between the first barium sulfate particles and the second barium sulfate particles may be 100 nm or more, but is not limited thereto.

[0022] In one embodiment, the weight ratio of the first barium sulfate particles to the second barium sulfate particles may be 10-90:90-10, but is not limited thereto.

[0023] In one embodiment, the coating layer may have a weight ratio of barium sulfate particles to a nitrogen-containing water-soluble polymer of 50:50 to 99.9:0.1, but is not limited thereto.

[0024] In one embodiment, the coating layer may further include any one or more resins selected from the group consisting of polyvinyl acetate, acrylic resin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polymethyl methacrylate, polyacrylonitrile, ethylene-vinyl acetate copolymer, carboxymethyl cellulose, and polyimide, but is not limited thereto.

[0025] In one embodiment, the thickness of the coating layer may be 0.1 to 50% of the total thickness of the separator, but is not limited thereto.

[0026] In one embodiment, the coating layer has a thickness of 0.5 to 10 g / m 2 The present invention is not limited to the above.

[0027] In one embodiment, the porous substrate may be a laminate of one or more materials selected from the group consisting of a porous film, a nonwoven fabric, and a woven fabric, but is not limited thereto.

[0028] In one embodiment, the porous substrate may have a thickness of 1 to 80 μm, but is not limited thereto.

[0029] Another aspect of the present disclosure provides a lithium secondary battery including the separator according to the above aspect. Effect of the Invention

[0030] The separator according to one embodiment of the present disclosure can provide the effects of low thermal shrinkage, excellent transmittance, and excellent adhesiveness.

[0031] In addition, a lithium secondary battery using a separator according to an embodiment of the present disclosure can provide the effects of having a high capacity retention rate during high-temperature storage and a small increase in resistance, and thus excellent high-temperature storage stability.

[0032] In addition, a lithium secondary battery using a separator according to an embodiment of the present disclosure has a high capacity retention rate and a low resistance increase rate in 400 cycle characteristics, and can provide excellent effects in long-term storage stability and long-term battery capacity.

[0033] Furthermore, a lithium secondary battery using a separator according to one embodiment of the present disclosure can provide the effect of significantly reducing the amount of gas generated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The present disclosure will now be described in detail, but this is for illustrative purposes only and is not intended to be limited to the specific embodiments described by way of example.

[0035] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. The terms used in the description of this disclosure are merely for the purpose of effectively describing specific embodiments and are not intended to limit the disclosure.

[0036] Additionally, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0037] In addition, when a part "comprises" certain elements, this means that it may further include other elements, rather than excluding other elements, unless otherwise specified to the contrary.

[0038] In addition, unless otherwise defined, when a layer or member is said to be "on" another layer or member, this includes not only the case where a layer or member is in contact with the other layer or member, but also the case where another layer or member exists between two layers or two members.

[0039] In addition, terms such as "about," "substantially," and the like are used to mean a numerical value or a approximation of a numerical value when manufacturing and material tolerances inherent in the referred meaning are given, and are used to prevent unconscionable infringers from unfairly taking advantage of the disclosure in which precise or absolute numerical values ​​are referred to for the understanding of the present disclosure.

[0040] In addition, the "average particle size" is "D 50 " means "D 50 " means the particle size of inorganic particles equivalent to 50% of the cumulative distribution on a volume basis. The average particle size can be derived from the particle size distribution results obtained by taking samples of the particles to be measured in accordance with the KS A ISO13320-1 standard and analyzing them using a Beckman Coulter Multisizer 4e Coulter counter.

[0041] In this disclosure, glass-transition temperature (Tg) refers to the temperature range in which a glass transition occurs, and refers to a value measured using a dilatometer or a differential scanning calorimeter (DSC).

[0042] Unless otherwise limited in the present disclosure, the weight average molecular weight (Mw), number average molecular weight (Mn), and viscosity average molecular weight (Mv) can be measured by methods known in the art, for example, the molecular weight in terms of polyethylene glycol analyzed by GPC (gel permeation chromatograph).

[0043] In the present disclosure, "as a main component" means that it is used as a major component compared to other components, and means that it is used in an amount of, for example, 50% by weight or more, more specifically 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 90% by weight or more, or 99% by weight or more.

[0044] According to one aspect of the present disclosure, a separator having excellent heat resistance, adhesive strength, and breathability can be provided by forming a coating layer using a composition that combines a specific binder and specific inorganic particles. When the separator is used, the amount of gas generated from a lithium secondary battery can be significantly reduced, and a lithium secondary battery having improved high-temperature storage characteristics and long-term life characteristics can be provided.

[0045] One aspect of the present disclosure provides a separator including a porous substrate and a coating layer formed on one or both sides of the porous substrate, the coating layer including a nitrogen-containing water-soluble polymer and barium sulfate particles.

[0046] A first aspect of the separator according to the present disclosure is a separator including a porous substrate and a coating layer formed on one or both sides of the porous substrate, the coating layer including a nitrogen-containing water-soluble polymer and barium sulfate particles.

[0047] A second embodiment is a separator including a porous substrate and a coating layer formed on one or both sides of the porous substrate, the coating layer including a nitrogen-containing water-soluble polymer and barium sulfate particles, as well as other inorganic particles such as boehmite particles.

[0048] A third aspect is a separator including a porous substrate and a coating layer formed on one or both sides of the porous substrate, the coating layer including a nitrogen-containing water-soluble polymer and two or more types of barium sulfate particles having different average particle sizes.

[0049] The first to third embodiments are merely exemplified to explain one embodiment of the present invention, and the present invention is not limited thereto. In addition, another layer may be further included between the porous substrate and the coating layer, and the type of the further included layer is not particularly limited. In addition, the coating layer may be a laminate of two or more coating layers of different types, and the present invention is not limited thereto.

[0050] Each configuration of the present disclosure will be described in more detail below.

[0051] [Porous base material] In one embodiment, the porous substrate may be a substrate commonly used in the art, such as a woven fabric, a nonwoven fabric, or a porous film, and may be a laminate of one or more selected from the above, but is not limited thereto.

[0052] The material of the porous substrate is not limited, and examples of the material that can be used include polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene. The porous substrate may be made of one or more resins selected from the group consisting of these.

[0053] For example, the porous substrate may be a polyolefin-based porous substrate that can be adjusted to have finer pores, but is not limited thereto. The polyolefin-based porous substrate is generally manufactured in the form of a film and is not limited to any material that is generally used as a separator for a lithium secondary battery, and examples of the porous substrate include, but are not limited to, polyethylene, polypropylene, and copolymers thereof.

[0054] The thickness of the porous substrate is not particularly limited, but from the viewpoint of increasing the capacity of a lithium secondary battery with the same volume, the thickness may be 100 μm or less, 90 μm or less, 80 μm or less, 1 μm or more, 5 μm or more, or any value between the above numerical values, for example, 1 to 80 μm, 1 to 70 μm, 5 to 50 μm, or 5 to 30 μm.

[0055] [Coating layer] The separator of the present disclosure includes a coating layer on one or both sides of the porous substrate.

[0056] In one embodiment, the coating layer may be coated to cover an area of ​​50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or 100% of the area of ​​the porous substrate.

[0057] The thickness of the coating layer is not particularly limited, and may be in the range of 0.1 to 50%, 0.5 to 45%, or 1 to 40% of the total thickness of the separator. For example, when the coating layer is formed on one side or both sides, each coating thickness may be 0.01 to 10 μm, 0.1 to 10 μm, 0.3 to 8 μm, 0.3 to 5 μm, or 1 to 4 μm, but is not limited thereto.

[0058] The weight per unit area of ​​the coating layer is 0.5 to 100 g / m 2 , 0.5~50g / m 2 , 0.5~10g / m 2 , 0.5~8g / m 2, or 0.5 to 5 g / m 2 It may be, but is not necessarily limited to this.

[0059] In one embodiment, the coating layer may be formed of inorganic particles and a nitrogen-containing water-soluble polymer, and the inorganic particles may be connected to each other to form pores between the inorganic particles. For example, the inorganic particles may be barium sulfate particles, and the barium sulfate particles may be connected to each other to form pores between the barium sulfate particles.

[0060] The coating layer may have a weight ratio of inorganic particles to nitrogen-containing water-soluble polymer of 50-99.9:50-0.1, 80-99.9:20-0.1, 90-99:10-1, or 95-99:5-1, but is not limited thereto. When the ratio is within the above range, lithium ions can be smoothly transferred, heat resistance can be exhibited, and a separator with a small thermal shrinkage rate can be provided, which is preferable, but is not limited thereto.

[0061] In one embodiment, the coating layer may be formed by applying a slurry composition containing inorganic particles and a nitrogen-containing water-soluble polymer, for example, the slurry composition may contain inorganic particles, a nitrogen-containing water-soluble polymer, and a solvent, and may have a solid content of 5 to 50 wt%, 5 to 45 wt%, or 5 to 40 wt%, but is not limited thereto.

[0062] In one embodiment, the nitrogen-containing water-soluble polymer can bind the inorganic particles to each other and to the porous substrate, and can also fulfill both the high-temperature storage characteristics and long-term life characteristics of the lithium secondary battery of the present disclosure, and can also significantly reduce the amount of gas generation.

[0063] In one embodiment of the present disclosure, the nitrogen-containing water-soluble polymer may include any one or more selected from the group consisting of polyvinylpyrrolidone, polyvinylpyrrolidone-based copolymers, and polyacrylamide-based resins.

[0064] In one embodiment, the nitrogen-containing water-soluble polymer may include a polyacrylamide resin, or may be a mixture of the polyacrylamide resin and one or more selected from polyvinylpyrrolidone and polyvinylpyrrolidone copolymers. In one embodiment, when the nitrogen-containing water-soluble polymer is a mixture of a polyacrylamide resin and one or more selected from polyvinylpyrrolidone and polyvinylpyrrolidone copolymers, the content of the polyacrylamide resin may be such that it is used as a main component. That is, the polyacrylamide resin may be used in an amount of 50% by weight or more, for example, 50 to 99.9% by weight, based on the content of the nitrogen-containing water-soluble polymer.

[0065] The polyvinylpyrrolidone may have a weight average molecular weight (Mw) of, for example, 10,000 to 1,000,000 g / mol, 20,000 to 900,000 g / mol, 30,000 to 700,000 g / mol, or 40,000 to 500,000 g / mol, but is not limited thereto. When it is within the above range, it is advantageous to achieve the intended effect, but is not limited thereto.

[0066] The polyvinylpyrrolidone copolymer includes a unit derived from N-vinyl-2-pyrrolidone and a unit derived from a comonomer, and the comonomer may be any one or a mixture of two or more selected from the group consisting of an aromatic vinyl monomer; a vinyl cyanide monomer; an aromatic (meth)acrylate having an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 20 carbon atoms; a hydroxyl group-containing (meth)acrylate; an epoxy group-containing (meth)acrylate; an unsaturated carboxylic acid; and the like, but is not limited thereto.

[0067] For example, the comonomer may be an aromatic vinyl monomer such as styrene, p-methylstyrene, m-methylstyrene, p-ethylstyrene, m-ethylstyrene, p-chlorostyrene, m-chlorostyrene, p-chloromethylstyrene, m-chloromethylstyrene, vinyltoluene, or vinylnaphthalene; a vinyl cyanide monomer such as acrylonitrile or methacrylonitrile; or a carbon monomer such as phenyl(meth)acrylate, benzyl(meth)acrylate, 2-phenylethyl(meth)acrylate, 3-phenylpropyl(meth)acrylate, 4-phenylbutyl(meth)acrylate, 2-2-methylphenylethyl(meth)acrylate, 2-3-methylphenylethyl(meth)acrylate, or 2-4-methylphenylethyl(meth)acrylate. The monomer may be any one or a mixture of two or more selected from the group consisting of, but is not limited to, aromatic (meth)acrylates having an aryl group, alkylaryl group, or arylalkyl group with a prime number of 6 to 20; hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 1,4-cyclohexanedimethanol mono(meth)acrylate; epoxy group-containing (meth)acrylates such as glycidyl acrylate and glycidyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; and vinyl acetate.

[0068] In addition, the polyvinylpyrrolidone copolymer may be, for example, a polyvinylpyrrolidone-polyvinyl acetate block copolymer, but is not limited thereto.

[0069] The polyvinylpyrrolidone copolymer may have a weight average molecular weight (Mw) of, for example, 10,000 to 1,000,000 g / mol, 50,000 to 900,000 g / mol, or 50,000 to 500,000 g / mol, but is not limited thereto. When it is within the above range, it is advantageous to achieve the intended effect, but is not limited thereto.

[0070] In one embodiment, the polyacrylamide resin may be a copolymer containing a structural unit derived from a (meth)acrylamide monomer.

[0071] For example, it may be a copolymer of a (meth)acrylamide-based monomer and a comonomer, and examples of the comonomer may be any one or more selected from (meth)acrylic acid, a (meth)acrylic monomer containing a hydroxyl group, a polyfunctional (meth)acrylamide-based monomer, etc., but are not limited thereto.

[0072] In one embodiment, the polyacrylamide resin may be a ternary copolymer, and may include, for example, (a) a structural unit derived from a (meth)acrylamide monomer, (b) a structural unit derived from a (meth)acryl monomer containing a hydroxy group, and (c) a structural unit derived from a polyfunctional (meth)acrylamide monomer.

[0073] The coating layer may further contain a heat-resistant binder or a moisture-acidic binder as a binder component, as necessary, which is generally used in the art. In terms of achieving the above-mentioned effects, it is preferable that the binder component contains the nitrogen-containing water-soluble polymer as a main component. The term "main component" means that the nitrogen-containing water-soluble polymer is used in an amount of 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 100% by weight, or any range between the above values, based on the total content of the binder. For example, the nitrogen-containing water-soluble polymer may be contained in an amount of 80 to 100% by weight, 85 to 100% by weight, 90 to 100% by weight, 95 to 100% by weight, or 98 to 100% by weight in the binder component forming the coating layer.

[0074] The heat-resistant binder or moisture-acidic binder that can be added additionally may be any binder that is generally used for binding inorganic particles in a separator, and may include, for example, one or more resins selected from the group consisting of polyvinyl acetate, acrylic resins, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymers, polyvinylidene fluoride-trichloroethylene copolymers, polyvinylidene fluoride-chlorotrifluoroethylene copolymers, polymethyl methacrylate, polyacrylonitrile, ethylene-vinyl acetate copolymers, carboxymethyl cellulose, polyimides, etc.

[0075] The nitrogen-containing water-soluble polymer may include a polyacrylamide resin, and in one embodiment, the polyacrylamide resin may be a copolymer including a structural unit derived from a (meth)acrylamide monomer.

[0076] For example, it may be a copolymer of a (meth)acrylamide-based monomer and a comonomer, and examples of the comonomer may be any one or more selected from (meth)acrylic acid, a (meth)acrylic monomer containing a hydroxyl group, a polyfunctional (meth)acrylamide-based monomer, etc., but are not limited thereto.

[0077] In one embodiment, the polyacrylamide resin may include (a) a structural unit derived from a (meth)acrylamide monomer, (b) a structural unit derived from a (meth)acryl monomer containing a hydroxy group, and (c) a structural unit derived from a polyfunctional (meth)acrylamide monomer. The (meth)acryl means acryl and / or methacryl.

[0078] The polyacrylamide resin can provide a separator with better heat resistance by using the above-mentioned ternary copolymer, which can further reduce the high temperature shrinkage rate and provide high temperature stability compared to the case of using a homopolymer derived from an acrylamide monomer, and can provide a separator with better adhesion to a porous substrate, and can provide a separator with better gas reduction effect by mixing with barium sulfate particles. In addition, the high temperature storage stability and high temperature capacity retention rate of a lithium secondary battery can be significantly improved.

[0079] In one embodiment, the polyacrylamide resin may contain (a) 65 to 96 mol % of structural units derived from a (meth)acrylamide monomer, (b) 3 to 34 mol % of structural units derived from a (meth)acryl monomer containing a hydroxy group, and (c) 0.001 to 1 mol % of structural units derived from a polyfunctional (meth)acrylamide monomer.

[0080] The (a) (meth)acrylamide-based monomer polymer unit of the polyacrylamide-based resin may be represented by the following Chemical Formula 1.

[0081] [ka]

[0082] In the above Chemical Formula 1, R1 is hydrogen or a C1 to C6 alkyl group.

[0083] The (b) polymerized unit of a (meth)acrylic monomer having a hydroxy group of the polyacrylamide resin can be represented by the following Chemical Formula 2.

[0084] [ka]

[0085] In the above Chemical Formula 2, R2 is hydrogen or a C1 to C6 alkyl group, and L1 is a C1 to C6 linear or branched alkylene group.

[0086] The (c) polyfunctional (meth)acrylamide monomer polymerized unit may be produced by polymerization of a polyfunctional monomer represented by the following Chemical Formula 3:

[0087] [ka]

[0088] In the above Chemical Formula 3, R1 and R2 are each independently hydrogen or a C1-C6 alkyl group, R may be a C1-C10 linear or branched hydrocarbon group, and a may be 2-6.

[0089] For example, (a) (meth)acrylamide monomer may be 65-96 mol%, 66-95 mol%, 67-94 mol%, 68-93 mol%, or 70.5-91.5 mol%, (b) hydroxyl group-containing (meth)acryl monomer may be 3-34 mol%, 4-33 mol%, 5-32 mol%, 6-31 mol%, or 8-29 mol%, and (c) polyfunctional (meth)acrylamide monomer may be 0.001-1 mol%, 0.005-0.9 mol%, or 0.01-0.5 mol%.

[0090] As an example, the polyacrylamide resin may be a cross-linked copolymer of acrylamide, hydroxyethyl acrylate, and N-methylenebisacrylamide, but is not limited thereto.

[0091] The weight average molecular weight of the polyacrylamide resin may be 100,000 g / mol or more, 150,000 g / mol or more, 200,000 g / mol or more, 250,000 g / mol or more, 2 million g / mol or less, 1.5 million g / mol or less, 1 million g / mol or less, or any value between the above values. For example, it may be 100,000 to 2 million g / mol. When the above range is satisfied, the adhesive strength with the porous substrate is more excellent, the thermal shrinkage rate can be further reduced, and the high temperature storage stability and capacity retention rate of the lithium secondary battery can be further improved, which is preferable, but is not limited thereto. The weight average molecular weight is an average molecular weight in terms of polyethylene glycol measured using gel permeation chromatography (GPC).

[0092] The polyacrylamide resin may have a viscosity of 3000 cps or less, 2500 cps or less, 2000 cps or less, or 1500 cps or less when the polyacrylamide resin has a solid content of 10 wt%, but is not limited thereto. When the polyacrylamide resin is mixed with inorganic particles in the above range to prepare a slurry, the viscosity of the slurry can be further reduced and the coatability can be further improved, which is desirable.

[0093] In one embodiment, the solvent used in the slurry composition produced for forming the coating layer may be, for example, a solution produced using water, and if necessary, a solvent such as acetone, tetrahydrofuran, dimethylformamide, or N-methyl-2-pyrrolidone may be further added.

[0094] In one embodiment, the inorganic particles can be any inorganic particles that are electrochemically stable and are commonly used to improve the heat resistance and heat shrinkage rate of a separator, without any limitations.

[0095] In one embodiment, the present disclosure may essentially include barium sulfate particles as inorganic particles. By mixing the barium sulfate particles with the water-soluble cross-linked polyacrylamide binder to form a coating layer, a separator having a more excellent gas reduction effect, high-temperature storage characteristics, and long-term life characteristics can be provided.

[0096] In addition to the barium sulfate, inorganic particles commonly used in the art may be further included, and the content of barium sulfate may be 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 100% by weight, or any range between the above values, based on the total content of the inorganic particles, for example, 50 to 100% by weight, 80 to 100% by weight, 90 to 100% by weight, 95 to 100% by weight, or 99 to 100% by weight.

[0097] Examples of inorganic particles that can be added in addition to the barium sulfate are not limited to inorganic particles commonly used in the art, and may further include one or more inorganic particles selected from, for example, boehmite, alumina, silica, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO3, SnO2, CeO2, NiO, ZnO, ZrO2, Y2O3, and SiC.

[0098] As an example, the coating layer of the present disclosure may use barium sulfate particles alone or a mixture of barium sulfate particles and boehmite particles as inorganic particles. By including these as essential components, the gas reduction effect can be more favorably achieved when mixed with the above-mentioned water-soluble composite binder. In addition, the high-temperature storage stability and capacity retention rate of the lithium secondary battery can be achieved. In this case, the mixing ratio is not limited, but the weight ratio of barium sulfate particles to boehmite particles may be 10 to 90:90 to 10.

[0099] The size of the inorganic particles usable in one embodiment of the present disclosure, including the barium sulfate particles, is not limited, but may be, for example, an average particle size of 50 nm or more, 100 nm or more, 200 nm or more, 300 nm or more, 1500 nm or less, 1000 nm or less, 800 nm or less, or any range between the above values, in order to provide smooth coating and excellent electrical properties. For example, the size may be in the range of 100 to 1500 nm, 200 nm to 1000 nm, or 300 to 800 nm. The shape of the inorganic particles is not limited, and may be spherical, elliptical, acicular, etc.

[0100] In one embodiment, the barium sulfate particles may be a mixture of two or more types of particles having different average particle sizes. For example, the barium sulfate particles may be a mixture of first barium sulfate particles having an average particle size of 200 to 500 nm and second barium sulfate particles having an average particle size of 500 to 1000 nm, and the difference in average particle size between the first barium sulfate particles and the second barium sulfate particles may be 100 nm or more, for example, 100 to 500 nm.

[0101] In one embodiment, other types of inorganic particles that can be added in addition to the barium sulfate particles may be used by mixing two or more types of particles with different average particle diameters. For example, when using two or more types of inorganic particles with different average particle diameters, a first inorganic particle with a relatively large average particle diameter and a second inorganic particle with a relatively small average particle diameter may be mixed and used, the first inorganic particle may have an average particle diameter of 200 to 500 nm, the second inorganic particle may have an average particle diameter of 500 to 1000 nm, and the difference in average particle diameter between the first inorganic particle and the second inorganic particle may be 100 nm or more, for example, 100 to 500 nm.

[0102] In one embodiment, the inorganic particles are mixed with a nitrogen-containing water-soluble polymer and a solvent to produce a slurry composition, and then the inorganic particles are sufficiently crushed using a ball mill or the like to pulverize the agglomerates.

[0103] In one embodiment, the coating layer may have a weight ratio of barium sulfate particles to a nitrogen-containing water-soluble polymer of 50:50 to 99.9:0.1, but is not limited thereto.

[0104] The method for coating the slurry composition on the porous substrate is not particularly limited, and various methods such as roll coating, spin coating, dip coating, bar coating, die coating, slit coating, inkjet printing, etc. may be used without limitation to coat one or both sides of the porous substrate.

[0105] The separator according to one embodiment of the present disclosure can exhibit a change in air permeability (ΔG) as shown in Formula 1 below.

[0106] [Formula 1] ΔG=G1-G2≦70

[0107] In the formula 1, G1 is the Gurley permeability of the separator including the coating layer, and G2 is the Gurley permeability of the porous substrate itself, measured in accordance with ASTM D726, with a unit of sec / 100cc.

[0108] In the formula 1, the ratio may be 70 sec / 100 cc or less, 60 sec / 100 cc or less, 50 sec / 100 cc or less, 1 to 70 sec / 100 cc, or 1 to 60 sec / 100 cc. When the ratio is within the above range, the change in air permeability is significantly small, and the air permeability of the binder can be excellent.

[0109] The separator according to one embodiment of the present disclosure may have a high temperature shrinkage rate measured when left in a hot air drying oven at 130°C for 60 minutes in both the machine direction and the width direction of 5% or less, 4% or less, 3% or less, 0.1% or more, 1% or more, or any value between the above values. For example, it may be 1 to 5%. When the above range is satisfied, a separator having excellent heat resistance and thermal stability can be provided. Furthermore, when the above range is satisfied, the gas reduction effect of the lithium secondary battery can be further excellent and the high temperature stability can be excellent.

[0110] In addition, the separator according to one embodiment of the present disclosure has excellent adhesive strength between the inorganic particles and the porous substrate, and can provide the effect of significantly reducing detachment of the inorganic particles.

[0111] [Lithium secondary battery] The lithium secondary battery according to one embodiment of the present disclosure may include the separator according to the above embodiment between the positive electrode and the negative electrode. In this case, the positive electrode and the negative electrode may be any electrode that is generally used in lithium secondary batteries without any limitations.

[0112] Although not limited thereto, the lithium secondary battery may include an electrolyte, for example, a liquid electrolyte, and the liquid electrolyte may include a dissociable lithium salt commonly used in the art and a non-aqueous solvent. The type of the lithium salt is not limited, but when the separator of the present disclosure is applied, the amount of gas generated can be particularly significantly reduced with an electrolyte containing LiPF6. However, the present disclosure is not limited thereto, and any commonly used electrolyte can be applied.

[0113] Hereinafter, the embodiments of the present disclosure will be further described with reference to specific experimental examples. The examples and comparative examples included in the experimental examples are merely illustrative of the present disclosure and do not limit the scope of the appended claims. It is obvious to those skilled in the art that various changes and modifications of the embodiments are possible within the scope of the scope and technical ideas of the present disclosure, and it goes without saying that such changes and modifications belong to the scope of the appended claims.

[0114] The physical properties were evaluated as follows:

[0115] [Weight average molecular weight] The measurements were performed using GPC (Tosoh Corporation's EcoSEC HLC-8320 GPC Reflective Index detector) with a TSKgel guard PWx, two TSKgel GMPWxl and a TSKgel G2500PWxl (7.8x300mm) as GPC columns, a 0.1M aqueous NaNO3 solution as the solvent and polyethylene glycol as the standard at 40°C and a flow rate of 1mL / min.

[0116] [Heat shrinkage evaluation] The separator was cut into a square with sides of 10 cm, and the transverse direction (TD) and machine direction (MD) were marked. The sample was placed in the center, and five sheets of paper were placed above and below the sample, and the four sides of the paper were wrapped with tape. The sample wrapped in paper was left in a hot air drying oven at 130°C for 60 minutes. The sample was then removed, the separator was measured with a camera, and the shrinkage rate in the length direction (MD, machine direction) and the shrinkage rate in the width direction (TD, transverse direction) were calculated using the following formula.

[0117] High temperature shrinkage rate in the longitudinal direction (%) = (length in the longitudinal direction before heating - length in the longitudinal direction after heating) / length in the longitudinal direction before heating × 100 High temperature shrinkage rate in the width direction (%) = (length in the width direction before heating - length in the width direction after heating) / length in the width direction before heating × 100

[0118] [Gurley Transmittance] The gas permeability was measured as Gurley permeability. It was measured using a Toyo Seiki Densometer in accordance with the ASTM D726 standard. The time it took for 100cc of air to pass through a separator with an area of ​​1 square inch was recorded in seconds and compared. The unit is sec / 100cc.

[0119] [Cardboard adhesion test] The separator was cut to a size of 50 mm x 50 mm and placed on the rubber pad with the inorganic layer facing down. A black cardboard (20 mm x 50 mm x T0.25 mm) was placed between the separator and the rubber pad, and a constant pressure (10 g / cm) was applied using a pressing device. 2 The black cardboard was forcibly removed from the side, and the degree of inorganic matter on the surface was checked. Depending on the degree of the matter, the following grades were used to determine whether the matter was A / B / C. A: Nothing attached B: A small amount of inorganic matter is attached C: Both binder and inorganic matter are attached [Thickness measurement method] Thickness of the separation membrane: After stacking 10 separation membranes, the thickness was measured at 5 random points in the width direction using a Mitutoyo thickness meter. The average thickness of the 10 layers of separation membranes was then calculated and divided by 10 again to calculate the average thickness of the entire single separation membrane. Thickness of porous substrate: The average thickness of the porous substrate was measured by stacking 10 layers of the porous substrate and then measuring the thickness at 5 arbitrary points in the width direction with a Mitutoyo thickness meter. The average thickness of the 10 layers of porous substrate was then calculated and divided by 10 again to calculate the average thickness of a single porous substrate. Coating layer thickness: Calculated as the average thickness of the entire isolation membrane obtained as described above minus the average thickness of the single porous substrate.

[0120] [Example 1] <Production of Slurry Composition> A slurry composition with a solids concentration of 30% by weight was produced by adding 97% by weight of barium sulfate having an average particle size of 500 nm and 3% by weight of a polyacrylamide resin (a cross-linked copolymer of acrylamide, hydroxyethyl acrylate, and N-methylenebisacrylamide, designated as "PAM1" in Table 1, with a weight-average molecular weight of 270,000 g / mol) to water as a solvent and stirring.

[0121] <Separator manufacturing> A separator (ENPASS, SK IE Technology) substrate with a width of 150 mm, length of 1000 m, and thickness of 9 μm was used. The coating solution prepared above was bar-coated on both sides of the substrate at a speed of 3 m / min to form a coating layer.

[0122] Thereafter, it was dried through a hot air dryer at 40° C. and wound up in a roll. The thickness of the coated separator measured after winding was 13 μm in total, and the thickness of the coating layer was 2 μm per side.

[0123] The physical properties of the produced separator were evaluated and are shown in Table 1 below.

[0124] <Manufacturing lithium secondary batteries> A homogeneous negative electrode slurry was prepared by adding 95% by weight of artificial graphite as the negative electrode active material, 3% by weight of acrylic latex (solid content 20% by weight) with a Tg of -52°C as a fusing agent (3% by weight), and 2% by weight of CMC (Carboxymethyl cellulose) as a thickener to water and stirring. The slurry was coated on a 20μm-thick copper foil, dried, and pressed to prepare a 150μm-thick negative electrode plate.

[0125] A homogeneous positive electrode slurry was prepared by adding 94% by weight of LiCoO2 as a positive electrode active material, 2.5% by weight of polyvinylidene fluoride as a fusing agent, and 3.5% by weight of carbon black as a conductive agent to a solvent, NMP (N-methyl-2-pyrrolidone), and stirring. The slurry was coated on a 30μm-thick aluminum foil, dried, and pressed to prepare a 150μm-thick positive electrode plate.

[0126] The separator was placed between the positive electrode and the negative electrode to prepare a pouch-type battery. An electrolyte containing 1M lithium hexafluorophosphate (LiPF6) dissolved therein and ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) = 25:45:20 (volume ratio) was added to the assembled battery. In order to seal the opening of the aluminum packaging material, a hit seal was performed at 165°C to close the aluminum exterior, and a 2 Ah pouch-type lithium secondary battery was prepared. The physical properties of the prepared battery were evaluated and are shown in Table 2.

[0127] [Example 2] The slurry composition was produced in the same manner as in Example 1, except that a mixture of boehmite and barium sulfate was used as the inorganic particles when producing the slurry composition.

[0128] That is, 60% by weight of barium sulfate having an average particle size of 500 nm, 37% by weight of boehmite (γ-AlO(OH)) having an average particle size of 600 nm, and 3% by weight of the polyacrylamide resin (represented as “PAM1” in Table 1) were added to water as a solvent and stirred to produce a slurry composition having a solid concentration of 30% by weight.

[0129] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0130] [Example 3] The slurry composition was produced in the same manner as in Example 1, except that two types of barium sulfate having different average particle sizes were used in producing the slurry composition.

[0131] That is, 50% by weight of barium sulfate having an average particle size of 800 nm, 47% by weight of barium sulfate having an average particle size of 500 nm, and 3% by weight of the polyacrylamide resin (referred to as "PAM1" in Table 1) were added to water as a solvent and stirred to produce a slurry composition having a solid concentration of 30% by weight.

[0132] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0133] [Example 4] The slurry composition was produced in the same manner as in Example 1, except that a polyacrylamide-based resin (referred to as "PAM2" in the table, a copolymer of acrylic acid and acrylamide, weight-average molecular weight of 100,000 g / mol) was used instead of the polyacrylamide-based resin (PAM1) in the production of the slurry composition.

[0134] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0135] [Example 5] The slurry composition was produced in the same manner as in Example 1, except that polyvinylpyrrolidone (PVP, manufactured by Sigma-Aldrich, CAS Number: 9003-39-8) was further contained as a binder when producing the slurry composition.

[0136] That is, 97% by weight of barium sulfate having an average particle size of 500 nm, 2% by weight of the polyacrylamide resin (referred to as "PAM1" in Table 1), and 1% by weight of polyvinylpyrrolidone (PVP, manufactured by Sigma-Aldrich Corporation, CAS Number: 9003-39-8) were added to water as a solvent and stirred to produce a slurry composition having a solid concentration of 30% by weight.

[0137] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0138] [Comparative Example 1] The slurry composition was produced in the same manner as in Example 1, except that a water-dispersed acrylic binder having a latex content of 20 wt% (containing 2 wt% polyvinyl alcohol having a melting temperature of 220°C and a saponification degree of 99%, and a Tg of -52°C) was used as the binder, and boehmite was used alone as the inorganic particles.

[0139] That is, 97% by weight of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3% by weight of an acrylic binder were added to water as a solvent and stirred to produce a slurry composition having a solid concentration of 30% by weight.

[0140] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0141] [Comparative Example 2] The slurry composition was produced in the same manner as in Example 1, except that boehmite was used instead of barium sulfate.

[0142] That is, 97% by weight of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3% by weight of the polyacrylamide resin (represented as “PAM1” in Table 1) were added to water as a solvent and stirred to produce a slurry composition having a solid concentration of 30% by weight.

[0143] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0144] [Comparative Example 3] The slurry composition was produced in the same manner as in Example 1, except that a polyacrylamide resin (referred to as "PAM2" in the table, a copolymer of acrylic acid and acrylamide, weight average molecular weight of 100,000 g / mol) was used and boehmite was used alone as the inorganic particles.

[0145] That is, 97% by weight of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3% by weight of polyacrylamide resin (PAM2) were added to water as a solvent and stirred to produce a slurry composition with a solid concentration of 30% by weight.

[0146] The physical properties of the produced separator and battery were evaluated and are shown in Tables 1 and 2.

[0147] [Table 1]

[0148] As shown in Table 1, Examples 1 to 5 according to one embodiment of the present disclosure had higher Gurley permeability, lower heat shrinkage, and no defects in the cardboard adhesion test compared to Comparative Examples 1 to 3.

[0149] In addition, a lithium secondary battery was manufactured using the prepared separator as described above, and its physical properties were measured.

[0150] [Initial resistance characteristics of lithium secondary batteries] Each battery manufactured through the assembly process of the examples and comparative examples was charged and then discharged at a constant current-constant voltage (CC-CV) of 4.2 V using a charge / discharge cycle device. Then, the direct current internal resistance (DC-IR) was measured by the J-Pulse method at a state of charge (SOC) of 60%.

[0151] [Storage stability at 60℃] Each battery (2 Ah cell) manufactured through the assembly process of the examples and comparative examples was stored in an oven at 60°C for 24 days, and then DC-IR (Direct Current Internal Resistance) was measured using the above-mentioned J-Pulse method, and the resistance increase rate was calculated. The resistance increase rate ΔR was calculated using the following formula. The resistance of each example and comparative example was evaluated relative to Comparative Example 1. The higher the value, the lower the relative resistance increase rate.

[0152] ΔR(%)=(R2-R1) / R1X100

[0153] The R1 is the initial resistance of each battery before the experiment, and the R2 is the resistance after storage at 60° C. for 28 days.

[0154] The capacity retention rate ΔC was calculated by the following formula. The capacity of each Example and Comparative Example was evaluated relatively with Comparative Example 1 as the standard. A higher value indicates a higher relative capacity retention rate.

[0155] ΔC(%)=[(discharge capacity after 28 days of oven storage - discharge capacity before oven storage)] / (discharge capacity before oven storage)]X100

[0156] [400 cycle life] Each of the batteries manufactured through the assembly process of the Example and Comparative Example was charged at a constant current-constant voltage (CC-CV) of 4.2 V and then discharged using a charge / discharge cycle device.

[0157] The lithium battery was charged at a constant current of 0.5C at 25°C until the voltage reached 4.2V, and then charged at a constant voltage of 0.01C while maintaining 4.2V. Then, the battery was discharged at a constant current of 0.5C until the voltage reached 3.0V, and this cycle was repeated 400 times. The capacity retention rate was calculated by measuring the discharge capacity at 400 cycles, and the resistance was calculated by measuring the DC-IR (Direct Current Internal Resistance) by the J-Pulse method and then calculating the resistance increase rate. The resistance of each Example and Comparative Example was evaluated relative to Comparative Example 1. The higher the value, the lower the relative resistance increase rate.

[0158] ΔR(%)=(R3-R1) / R1X100

[0159] The R1 is the initial resistance of each battery before the experiment, and the R3 is the resistance after 400 cycles.

[0160] The capacity retention rate ΔC was calculated by the following formula. The capacity of each Example and Comparative Example was evaluated relatively with Comparative Example 1 as the standard. A higher value indicates a higher relative capacity retention rate.

[0161] ΔC(%)=[(discharge capacity after 400 cycles-initial discharge capacity) / (initial discharge capacity)] / 100

[0162] [Gas generation analysis] The amount of gas generation was measured by preparing a 100% charged SOC battery, measuring its volume using a density meter, storing it in an oven at 60°C for 10 weeks, and then measuring the volume in the same manner. The volume change (volume increase rate ΔV) relative to the volume at 0 weeks of storage was calculated using the following formula. The volume change was evaluated in each Example and Comparative Example relative to Comparative Example 1. The lower the value, the less gas generation.

[0163] Volume increase rate ΔV (%) = [volume at 10 weeks - volume at 0 weeks) / volume at 0 weeks] × 100

[0164] As described above, the measured values ​​of Comparative Example 1 were used as the standard to relatively evaluate the physical properties of the batteries of the other Examples and Comparative Examples.

[0165] The results are shown in Table 2 below.

[0166] [Table 2]

[0167] As shown in Table 2, when the separators of Examples 1 to 5 according to one embodiment of the present disclosure are applied, the capacity retention rate during high-temperature storage of the battery is relatively high and the increase in resistance is small, compared to the case where an acrylic binder is applied as in Comparative Example 1, and therefore it was confirmed that the high-temperature storage stability is excellent. In addition, the capacity retention rate is high and the resistance increase rate is low in the 400-cycle characteristics, and therefore it was confirmed that the long-term battery characteristics are excellent. In addition, it was confirmed that the amount of gas generated is low.

[0168] Furthermore, Examples 1 to 5 used barium sulfate particles and showed even better physical properties than Comparative Examples 2 to 3, which used boehmite particles. From this, it was confirmed that the high-temperature storage characteristics and long-term life of a battery are improved by using a combination of a binder according to one embodiment of the present disclosure and barium sulfate particles.

[0169] What has been described above is merely illustrative of the application of the principles of the present disclosure, and other arrangements may be included without departing from the scope of the present invention.

[0170] As described above, the present disclosure has been described using specific matters and limited examples, but this is merely provided for a more general understanding of the present disclosure, and the present disclosure is not limited to the above examples. A person having ordinary knowledge in the field to which the present disclosure belongs can make various modifications and variations from such descriptions.

[0171] Therefore, the idea of ​​the present disclosure should not be limited to the above-described embodiments, and it can be said that not only the scope of the attached claims, but also anything that has an equivalent or equivalent modification to the scope of the claims falls within the scope of the idea of ​​the present disclosure.

Claims

1. A separator comprising a porous substrate and a coating layer on one or both sides of the porous substrate, The coating layer comprises a nitrogen-containing water-soluble polymer and barium sulfate particles.

2. 2. The separator according to claim 1, wherein the nitrogen-containing water-soluble polymer comprises at least one selected from the group consisting of polyvinylpyrrolidone, polyvinylpyrrolidone-based copolymers, and polyacrylamide-based resins.

3. 3. The separator according to claim 2, wherein the polyacrylamide resin is a polyacrylamide copolymer containing a unit derived from a (meth)acrylamide monomer and a unit derived from a comonomer.

4. 4. The separator according to claim 3, wherein the polyacrylamide resin comprises (a) a structural unit derived from a (meth)acrylamide monomer, (b) a structural unit derived from a (meth)acryl monomer containing a hydroxy group, and (c) a structural unit derived from a polyfunctional (meth)acrylamide monomer.

5. 3. The separator according to claim 2, wherein the polyacrylamide resin has a weight average molecular weight of 100,000 to 2,000,000 g / mol.

6. The coating layer may be formed of boehmite, alumina, silica, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO 3 , SnO 2 , CeO 2 , NiO, ZnO, ZrO 2 , Y 2 O 3 10. The separator of claim 1, further comprising one or more inorganic particles selected from:

7. The separator according to claim 1, wherein the barium sulfate particles have an average particle size of 200 to 1000 nm.

8. The separator according to claim 1 , wherein the barium sulfate particles are a mixture of two or more types of particles having different average particle sizes.

9. The barium sulfate particles are a mixture of first barium sulfate particles having an average particle size of 200 to 500 nm and second barium sulfate particles having an average particle size of 500 to 1000 nm, The separator according to claim 8 , wherein a difference in average particle size between the first barium sulfate particles and the second barium sulfate particles is 100 nm or more.

10. The separator according to claim 9, wherein a weight ratio of the first barium sulfate particles to the second barium sulfate particles is 10-90:90-10.

11. 2. The separator according to claim 1, wherein the coating layer has a weight ratio of barium sulfate particles to the nitrogen-containing water-soluble polymer of 50:50 to 99.9:0.

1.

12. 2. The separator according to claim 1, wherein the coating layer further comprises one or more resins selected from the group consisting of polyvinyl acetate, acrylic resin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polymethyl methacrylate, polyacrylonitrile, ethylene-vinyl acetate copolymer, carboxymethyl cellulose, and polyimide.

13. The separator according to claim 1 , wherein the thickness of the coating layer is 0.1 to 50% of the total thickness of the separator.

14. The coating layer has a thickness of 0.5 to 10 g / m 2 The separator of claim 1 formed of

15. The separator according to claim 1 , wherein the porous substrate is a laminate of one or more materials selected from the group consisting of a porous film, a nonwoven fabric, a woven fabric, and the like.

16. The separator according to claim 1 , wherein the porous substrate has a thickness of 1 to 80 μm.

17. A lithium secondary battery comprising the separator according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Anode for lithium secondary battery and methode of manufacturing the same

    KR102436898B1